Repeated high altitude training for the Sydney Olympic Games - Tachi, M.; Okuno, K.; Wakayoshi, K. (Biomechanics and Medicine in Swimming IX, 2003)
Today the advantage of high altitude training on swimming performance at sea level is widely known. The Japanese national swimming team has carried out high altitude training camps for about 20 years. Toward the Sydney Olympic Games, the national team also trained in high altitude (2134 m). Although they used to train at high altitude only once before each competition, this time they underwent two camps at an interval of a month between the Japan swimming championship (Olympic selection) and the Olympic Games. The first high altitude training camp was held to enhance the efficiency of the second training camp. The purpose of this study is to discuss the effects of repeated high altitude training from the results of competitions, swimming tests and blood samplings.